Some new insights of the characteristics of equatorial plasma bubbles obtained from Indian region. (April 2017) - Narayanan, V.L.; Gurubaran, S.; Shiny, M.B. Berlin; Emperumal, K.; Patil, P.T.
Abstract: All-sky imaging observations of OI 630.0 nm airglow were carried out in campaign mode from Panhala (16.8°N, 74.1°E geographic; 11.1°N dip latitude), India, during January to March 2008. On 14 of 37 nights, equatorial plasma bubbles were observed. The drift speeds were observed to decrease with time in concurrence with the previous results. The tilts were mostly westward while on rare occasions the plasma bubbles tilted eastwards. The drifts were found to be relatively lesser on disturbed nights while the tilts appear to be marginally larger. The interdepletion distances (or bubble spacings) also showed a decreasing trend with time till midnight indicating that the bubbles approach each other with the passage of time. Such a behavior is not reported earlier and it seems to have important implications for understanding the time evolution of plasma bubbles. On occasions, the bubbles occurred in groups. An ionosonde operating over Indian dip equatorial site Tirunelveli (1.1°N dip latitude) was used to study the variations in the base height of the ionosphere during the plasma bubble observations. The ionosonde measurements indicate lack of significant pre-reversal enhancement (PRE) during geomagnetic quiet days in which the bubbles were observed. Highlights: Observation of reduction in spacing between successive bubble pairs. The westward tilts of the bubbles are found to be comparatively higher during disturbed nights. Plasma bubbles were also observed on the days in which the pre-reversal enhancement was insignificant.